THE EVOLVING DIMENSIONS OF THE ACCOUNTING PROFESSION AND THE 21ST CENTURY EXPECTATIONS - Daferighe, Emmanuel Emeakponuzo (Archives of Business Research, 2019)
Abstract The dimension of the accountancy profession is undergoing an increasingly expanding and unpunctuated global evolution. These 21st-century twists, however, tend to pose an identity threat to the profession. The much-celebrated software substitution of the traditional roles of the Accountant coupled with the apparent professional cross-carpeting of non-accountants aided by these emerging digital initiatives appears to ‘take-over’ the seat of the Accountant. This paper begins with an overview of the cross-centurial evolution of the accounting thought to date. It also re-asserts the professional distinctiveness of the 21st-century Accountant by redefining and marking out his strategic essence in the light of the present day expectations. With an end to this evolution far from sight, the paper further reiterates the ACCA-recommended future imperatives of the accountancy profession. With the compendium of issues articulated in this paper, Accountants would be more orientated towards obtaining and maintaining a meaningful distinctive professional and global relevance in the coming days. Keywords: Accounting profession, 21st Century development, evolving dimensions, expectations